PENGARUH KOMPETENSI PAEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM DAN MOTIVASI BELAJAR PESERTA DIDIK TERHADAP PRESTASI BELAJAR SISWA DI MAS DAREL HIKMAH - Nur Wulandari Sunawir; Risnawati; M. Fikri Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to identify the extent to which the pedagogical competence possessed by PAI teachers and the motivation of students affect PAI learning outcomes. This research also aims to assess how strong this influence is if it is proven to have a positive and significant impact. The method used in this study is a survey with correlation and regression analysis. Data regarding the influence of PAI teachers' pedagogical competence and student motivation were collected through a questionnaire designed by the researcher, which measures aspects related to both variables. Meanwhile, data on PAI learning outcomes were obtained through tests conducted directly by the researcher. The analysis results indicate that the influence of PAI teachers' pedagogical competence and student motivation is reflected in a correlation coefficient of 0.762 and a coefficient of determination (r²) of 58.0%. The resulting regression equation is Y = 3.080 + 0.308 X1 + 0.254 X2. Through testing analysis, both the correlation coefficient and regression coefficient were found to be significant. This indicates that there is a significant influence of PAI teachers' pedagogical competence and student motivation simultaneously on PAI learning outcomes.